Developing academic writing skills as part of graduate attributes in undergraduate curricula - Du Preez, I (South African Journal of Higher Education, 2016)
The development of graduate attributes in higher education is enjoying much attention worldwide. Employers consistently rank communication skills, in particular writing ability, among the most important skills for graduates to possess. The inclusion and development of graduate attributes in undergraduate curricula have received little attention. In South Africa, the National Qualifications Framework provides level descriptors for the inclusion of generic graduate attributes at different educational levels in curricula. Level descriptors for academic writing are rather vague, and have not been explicitly addressed. We propose in this paper a possible process framework for the integration of the development of academic writing skills into an undergraduate four year degree in higher education. The vague writing level descriptors provided by South African National Qualifications Framework have been rewritten more specifically. Implementing these remodelled level descriptors for writing will facilitate the integration of academic writing skills into a four year bachelor’s degree. Keywords: Generic graduate attributes, embedded approach, curriculum mapping, undergraduates